Stakeholders debate Livestock Fish Mega Program proposal - Randolph, Thomas F. (International Livestock Research Institute, 2010)
Tom Randolph from ILRI reflects on the Livestock Fish Mega Program stakeholder consultation in Addis Ababa and the processes by which participants could test and debate the assumptions underlying the proposal. He was speaking in the margins of the CGIAR Livestock Fish Mega Program stakeholder consultation meeting in Addis Ababa, 24 and 25 August 2010.